93 Handover related anxiety. (30th November 2020) - Konstantinidou, Sevasti; Patel, Nikita; Sivaraj, Jayaram; Dhaiban, Manal; Wills, Dylan; Loukogeorgakis, Stavros; Jones, Ceri
Abstract : Background: Handover is a vital clinical skill to transfer information to ensure continuity of care for patients. However, handover can be stressful with significant effect on clinicians. It is important to acknowledge participants well-being and level of expectation. This project aims to assess and address handover as cause of anxiety for the clinical team. Methods: We have conducted a quality improvement project assessing the impact of handover to participants well-being, utilising a verified questionnaire. Following the results, changes were implemented to provide a standardised structure to handover, providing a framework and expectation for the process with an aim to improve clinicians' satisfaction and quality of handover. Results: Twenty questionnaires were initially completed regarding handover. Most of the participants felt that handover was a source of anxiety. Seventy-five percent of the consultant respondents felt anxiety related to time pressure and the need to attend to clinical and nonclinical responsibilities. The majority (66%) of the registrar respondents had anxiety related to leading and receiving handover. The junior team appeared to be the group less effected by handover. Following recognition of this and implementation of improvements, reported anxiety was reduced to 20% among all team members. Conclusions: We have identified the handover as a stressful period of the working day. The reason for anxiety is very interesting as it varies for different members of the team. Initial interventions had positive effect on participants. We aim to continue assessing, teaching 'handover communication skills' and refining handover process to improve mental health linked to handover.